Very high energy γ-ray emission from two blazars of unknown redshift and upper limits on their distance - Abdalla, Hassan; Glawion, Dorit; Jankowsky, Felix; Marx, Ramin; Mohamed, Mahmoud; Quirrenbach, Andreas; Schwemmer, Stephanie; Wagner, Stefan; Wierzcholska, Alicja (Monthly notices of the Royal Astronomical Society, 2020)
We report on the detection of very high energy (VHE; E > 100 GeV) γ -ray emission from the BL Lac objects KUV 00311−1938 and PKS 1440−389 with the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi/LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi/LAT spectrum towards the VHE γ -ray regime, we deduce a 95 per cent conﬁdence level upper limit on the unknown redshift of KUV 00311−1938 of z < 0.98 and of PKS 1440−389 of z < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311−1938 is constrained to 0.51 ≤ z < 0.98 and of PKS 1440−389 to 0.14 z < 0.53.